Payment of Court Fees Via Payment Service Providers - Wyżykowski, Bartosz (Journal of Finance and Financial Law, 2020)
The purpose of the article is to show that the date of initiating a payment order is decisive for meeting the deadline of payments of court fees in civil and administrative court proceedings, rather than the date of receipt of funds by the court (the date of crediting the court's account), regardless of the operator through which the transaction has been initiated provided that it a payment service provider. Subject of the analysis is in particular the overview of the current jurisprudence of the Supreme Court and the Supreme Administrative Court.